Dialectics of Trauma in the Short Stories of Alice Munro - Das, Shruti; Routray, Deepshikha (SCHOLARS: Journal of Arts & Humanities, 2021)
This paper argues that difficult relationships in human life followed by memories, introspection, retrospection, foreshadow, flashback, and awful remembrances are coloured by pain and trauma. Unresolved trauma affects the way one perceives others and oneself in relation to others, which has a significant impact on relationships and often results in behaviour that is not conducive to healthy relationships. Complicated, disordered feelings and distressing emotions that give rise to anxiety find an expression in relationships, either overtly or covertly. This paper will focus on how the characters, suffering from anxiety due to stressed relationships, in the short stories in The Progress of Love, written by Alice Munro, employ defence mechanisms to repress their trauma and project a different version of themselves as responsible individuals who are capable of leading a normal life. The dialectic of trauma covertly present in the narrative will be unravelled using Judith Herman’s theory of trauma. Further, this analysis will investigate and foreground how the underlying trauma finds indirect expression in complicated relationships.